Functional organic click-materials: application in phosphorescent organic light emitting diodes. Issue 20 (20th February 2017) - Kautny, Paul; Zhao, Chenyang; Kader, Thomas; Stöger, Berthold; Horkel, Ernst; Chen, Jiangshan; Ma, Dongge; Fröhlich, Johannes; Lumpi, Daniel
Abstract : 1, 2, 3-Triazole has been applied as a novel linker in donor–acceptor materials to control intramolecular charge transfer phenomena. Abstract : In the presented work click chemistry is utilized to introduce 1, 2, 3-triazoles as a functional linker in organic donor–acceptor materials. A systematic series of materials was prepared and characterized to investigate the effect of the linkage mode on the molecular properties. The 1, 2, 3-triazole linker allowed control of the degree of intramolecular charge transfer over a wide range depending on the substitution pattern of the triazole moiety. The prepared materials were successfully employed as host materials for green and red dopants in phosphorescent organic light emitting diodes. Thus, this work presents the first application of this novel linkage mode in the design and synthesis of functional π-conjugated organic donor–acceptor materials and their application in organic light emitting diodes.